ANALISIS KUALITATIF IMPLEMENTASI KEPDIRJENPENDIS NO. 1111 TAHUN 2019 TENTANG PETUNJUK TEKNIS PENILAIAN KINERJA KEPALA MADRASAH TSANAWIYAH NEGERI DI MASA PEMBELAJARAN DARING UNTUK PENGEMBANGAN MUTU MADARASAH - Deni Sunarya (Bajang Institute, 2021)
Qualitative Analysis of Implementation of Kepdirjenpendis No.IIII of 2019 concerning Technical Instructions for Performance Assessment to State Madrasah Tsanawiyah During the Online Learning Period for Efforts to Develop Madrasah Quality in Sukabumi Regency. The Head of Madrasah is one of the components of education that plays the most role in improving the quality of education as stated in Law Article 12 paragraph 1 PP 28 which states that